Activity-based protein profiling: The serine hydrolases - Liu, Yongsheng (The National Academy of Sciences, 1999)
With the postgenome era rapidly approaching, new strategies for the functional analysis of proteins are needed. To date, proteomics efforts have primarily been confined to recording variations in protein level rather than activity. The ability to profile classes of proteins on the basis of changes in their activity would greatly accelerate both the assignment of protein function and the identification of potential pharmaceutical targets. Here, we describe the chemical synthesis and utility of an active-site directed probe for visualizing dynamics in the expression and function of an entire enzyme family, the serine hydrolases. By reacting this probe, a biotinylated fluorophosphonate referred to as FP-biotin, with crude tissue extracts, we quickly and with high sensitivity detect numerous serine hydrolases, many of which display tissue-restricted patterns of expression. Additionally, we show that FP-biotin labels these proteins in an activity-dependent manner that can be followed kinetically, offering a powerful means to monitor dynamics simultaneously in both protein function and expression.